2000
DOI: 10.1161/01.str.31.12.3034
|View full text |Cite
|
Sign up to set email alerts
|

Metalloproteinase Inhibition Reduces Thrombolytic (Tissue Plasminogen Activator)–Induced Hemorrhage After Thromboembolic Stroke

Abstract: Background and Purpose-A potentially dangerous side effect associated with tissue plasminogen activator (tPA) use is cerebral hemorrhage. We have focused on developing drugs that could be administered with tPA to reduce the rate of hemorrhage. Since recent studies suggest that various matrix metalloproteinases (MMPs) are important in tumor necrosis factor-␣ production and membrane and vessel remodeling after ischemia, we investigated whether MMP inhibition affected the rate of hemorrhage and infarct production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
262
1
7

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 315 publications
(283 citation statements)
references
References 38 publications
13
262
1
7
Order By: Relevance
“…Studies in nonhuman primates have shown that the levels of MMP-9 were associated with hemorrhagic transformation, while MMP-2 correlated with neuronal injury (Heo et al, 1999). A recent study showed that hemorrhagic infarctions, induced in rabbits by the injection of autologous blood clots into the carotid, were reduced by treatment with the MMP inhibitor, Batimistat (BB-94) (Lapchak et al, 2000).…”
Section: Role Of the Mmps In Neuroinflammation In Cerebral Ischemiamentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in nonhuman primates have shown that the levels of MMP-9 were associated with hemorrhagic transformation, while MMP-2 correlated with neuronal injury (Heo et al, 1999). A recent study showed that hemorrhagic infarctions, induced in rabbits by the injection of autologous blood clots into the carotid, were reduced by treatment with the MMP inhibitor, Batimistat (BB-94) (Lapchak et al, 2000).…”
Section: Role Of the Mmps In Neuroinflammation In Cerebral Ischemiamentioning
confidence: 99%
“…Treatments in several animal models of neurological diseases have produced encouraging results. These include intracerebral hemorrhage, experimental allergic neuritis, delayed hypersensitivity, and bacterial meningitis (Rosenberg and Navratil, 1997;Hughes et al, 1998;Lapchak et al, 2000;Leib et al, 2001).…”
Section: Synthetic Mmp Inhibitorsmentioning
confidence: 99%
“…In the past, efforts to ameliorate MMP-mediated brain damage with broad-spectrum MMP inhibitors (like sulfonamide or hydroxamate derivatives) have produced promising results in animal models of stroke (Asahi et al, 2000;Lapchak et al, 2000). However, the low specificity, and thus systemic toxicity, of hydroxamates and sulfonamides have precluded the use of these broad-spectrum inhibitors in clinical studies (Coussens et al, 2002;Overall and Lopez-Otin, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…MMPs are also involved in the hemorrhagic transformation after cerebral ischemia, especially after thrombolysis (Hosomi et al, 2001;Montaner et al, 2003;Sumii and Lo 2002). Hemorrhagic transformation is closely related to levels of plasma MMP-9 (Castellanos et al, 2003), and MMP inhibitors can reduce hemorrhage after thromboembolic stroke (Lapchak et al, 2000). MMPs are further associated with derangement of blood-brain barrier (Rosenberg et al, 1998), and MMP inhibition reduces brain edema after ICH (Rosenberg and Navratil, 1997).…”
mentioning
confidence: 99%